Comparison of a Smartphone Otoscope and Conventional Otoscope in the Diagnosis and Management of Acute Otitis Media. (March 2019) - Chan, K. Ning; Silverstein, Anna; Bryan, Leah N.; McCracken, Courtney E.; Little, Wendalyn K.; Shane, Andi L.
Acute otitis media (AOM) is a leading cause of health encounters and antimicrobial prescriptions in children worldwide. We assessed (1) the rates of antimicrobial prescribing by pediatric emergency department clinicians using a smartphone otoscope device as compared with a conventional otoscope and (2) clinician acceptability of the smartphone device. We conducted a randomized control study in children's hospital emergency departments over 6 months. More than 1500 encounters were analyzed. The odds of prescribing antibiotics after being given a diagnosis of AOM by clinicians assigned to the smartphone group was 11% higher than the conventional group (18.8% vs 18.0%, odds ratio = 1.106, P = .600). Eight (73%) of the 11 physicians in the smartphone group preferred the smartphone device over the conventional otoscope. Use of a smartphone otoscope for detection of AOM in a pediatric emergency department setting did not lead to an increased likelihood of AOM diagnosis.